Heavy metals concentration in the sediment of the aquatic environment caused by the leachate discharge from a landfill - L. Sulistyowati; N. Nurhasanah; E. Riani; M. Cordova (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Heavy metals are categorized as hazardous pollutants due to their incapability in decomposing and undergoing bioaccumulation and biomagnification. Heavy metal pollution is a global issue, particularly in emerging nations such as Indonesia. In this case, sediments contribute to pollution dispersion because they can transport, mobilize, and redistribute toxic compounds. The Cisadane river is one of 15 watersheds in Indonesia with the highest restoration priority. Therefore, it is essential to conduct study on the sediment quality of this river. This investigation aimed to evaluate the levels of cadmium, chromium, and lead in the sediments to assess the conditions of the Cisadane River.METHODS: At eight stations (representing the midstream and downstream region), surface sediment samples were collected using a van Veen sediment grab based on the hypothesis that heavy metal pollution originated from land-based activities and migrated down river estuaries. The Thermo Scientific iCAP 7400 was utilized to assess heavy metals (cadmium, chromium, and lead) by adopting prior research methodologies and method guidelines.FINDINGS: Except for lead, which surpassed the interim sediment quality standard, the levels of heavy metals observed in the midstream and downstream sections of the Cisadane River were found to be well below the guideline level. In this case, lead was the metal with the highest concentration in the sediments of the Cisadane River, followed by chromium and cadmium. The enrichment of heavy metals in river sediments was most likely caused by soil leaching, municipal and industrial sewage, as well as land waste disposal. After the landfill area, there were two areas with the highest concentration. Therefore, this investigation indicated the existence of landfills as point sources of heavy metals. Regarding specifics, two sites following the landfill constitute the apex of heavy metal amplification.CONCLUSION:  This analysis shows that the sediment's cadmium, chromium, and lead contents are below the standards' threshold and safe for the habitat. Cadmium, chromium and lead exceed sediment quality requirements in sample sites after landfills, assumed to be due to leachate discharge and landfill activities. This study further also reveals that landfills are point sources of heavy metals. In this case, the heavy metals are two to four times higher in one kilometer from the landfill's leachate discharge. Therefore, the Enforcement of the Indonesia Waste Law Number 18 Year 2008 would have replaced unsanitary dumping including implementation of physicochemical, biological, and combination remediation techniques, with a vastly superior waste management system.